Textural characterization of micro- and mesoporous carbons using combined gas adsorption and n -nonane preadsorption - Oschatz, Martin; Borchardt, Lars; Rico-Frances, Soledad; Rodriguez-Reinoso, Francisco; Kaskel, Stefan; Sivestre-Abero, Joaquin (Langmuir, 2013)
Porous carbon and carbide materials with different structures were characterized using adsorption of nitrogen at 77.4 K before and after preadsorption of n-nonane. The selective blocking of the microporosity with n-nonane shows that ordered mesoporous silicon carbide material (OM-SiC) is almost exclusively mesoporous whereas the ordered mesoporous carbon CMK-3 contains a significant amount of micropores (∼25%). The insertion of micropores into OM-SiC using selective extraction of silicon by hot chlorine gas leads to the formation of ordered mesoporous carbide-derived carbon (OM-CDC) with a hierarchical pore structure and significantly higher micropore volume as compared to CMK-3, whereas a CDC material from a nonporous precursor is exclusively microporous. Volumes of narrow micropores, calculated by adsorption of carbon dioxide at 273 K, are in linear correlation with the volumes blocked by n-nonane. Argon adsorption measurements at 87.3 K allow for precise and reliable calculation of the pore size distribution of the materials using density functional theory (DFT) methods. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20